Analysis Of The Development Of Cultural Tourism Villages In The Kacirebonan Palace - Setiawan, Agung; Setiawati, Ety (Ann Publisher, 2024)
Research has been carried out to analyze the development of cultural tourism villages in the Kacirebonan Palace. The method used is descriptive with informants of palace relatives, interviews, surveys, and literature reviews. The results showed that Cultural tourism villages in the Kacirebonan Palace can be carried out with various kinds of supporters, such as the customs of the Kacirebonan Palace and the activities carried out by the Kacirebonan Palace, such as Suraan, Safaran, Syawalan, Pajang Talisman Tradition, and Ngisis Wayang tradition, which is the main potential in the development of the cultural wisest villages in the Kacirebonan Palace. In addition to the potential found in the Kacirebonan Palace, it is also supported by the potential owned by the Cultural Village, such as the existence of the Sekar Pandan dance studio, the existence of the Cultural Tourism Village Art Museum, the existence of carving houses in the Cultural Tourism Village and the existence of buildings that have value and history around the Kacirebonan Palace Cultural Tourism Village. In addition to the potential possessed by the cultural tourism village of the Kacirebonan Palace, the most important thing is the involvement of the community in the cultural tourism village, which is a benchmark and also a strategic factor in the development of the cultural tourism village at the Kacirebonan Palace. The cultural tourism village of the Kacirebonan Palace requires togetherness in the management of the cultural tourism village through the common perception between crocodile tourism village activists and the community so that they will be more comfortable in running the cultural tourism village at the Kacirebonan Palace. It is necessary to make tour packages regarding the cultural tourism village of the Kacirebonan Palace, both those that can be done every day and those that are related to activities involving the activities of the Kacirebonan Palace, so that it will further enrich the tour packages that tourists can enjoy if they visit the Cultural Tourism Village of the Kacirebonan Palace. There is participation from academics to participate in the development of cultural tourism villages in terms of human resource training such as tourism awareness training, training in the management tourism villages, as well as assistance in the homestay creation plan, which will be initiated first by Elang Iyan Ariffudin.